Strategies for Assessing the Unique Strengths, Needs, and Visions of Rural Science Teachers - Gail Shroyer; Larry Enochs (Journal of Research in Rural Education, 1986)
The authors present those strategies developed for a National Science Foundation grant to improve rural science education. The aim of these strategies was to encourage rural teachers to identify their unique and diverse strengths and weaknesses and to use this assessment to build a vision of the future for their school's science program. These strategies, unified in the form of an "action plan," provide a methodological model for other projects aimed at improving rural education.